2010
DOI: 10.1007/s00436-010-2148-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure analysis of ITS2 in the rDNA of three Indian paramphistomid species found in local livestock

Abstract: Of paramphistomid trematodes, three species viz., Homalogaster paloniae, Calicophoron calicophorum and Orthocoelium streptocoelium are commonly prevalent in bovine hosts in Northeast India. The aim of the present study was to genetically characterise these species using rDNA second internal transcribed spacer (ITS2) so as to supplement the morphological criteria substantiated by molecular findings. The annotated ITS2 region from H. paloniae, C. calicophorum and O. streptocoelium were found to be 289 bp, 288 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Miura et al (2005) reported the absence of heterozygosity in ITS-1 genes, which did not provide any support of gene fl ow among different lineages. Some workers suggested the ITS-2 as effective marker for species identifi cation, phylogenetic relations and developmental stages as well as molecular epidemiology and infection control (Rinaldi et al, 2005;Curran et al, 2006;Bazsalovicsová et al, 2010;Lotfy et al, 2010;Shylla et al, 2011;Ghatani et al, 2012;Phalee et al, 2014;Bian et al, 2013;Portier et al, 2012). In helminth parasites, ITS pseudogenes and mitochondrial genes are present and identifi cation of ITS region is not easy due to non-protein coding nature as compared to mitochondrial genes (Benasson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Miura et al (2005) reported the absence of heterozygosity in ITS-1 genes, which did not provide any support of gene fl ow among different lineages. Some workers suggested the ITS-2 as effective marker for species identifi cation, phylogenetic relations and developmental stages as well as molecular epidemiology and infection control (Rinaldi et al, 2005;Curran et al, 2006;Bazsalovicsová et al, 2010;Lotfy et al, 2010;Shylla et al, 2011;Ghatani et al, 2012;Phalee et al, 2014;Bian et al, 2013;Portier et al, 2012). In helminth parasites, ITS pseudogenes and mitochondrial genes are present and identifi cation of ITS region is not easy due to non-protein coding nature as compared to mitochondrial genes (Benasson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In Indian subcontinent major studies have been conducted only on the Fasciolidae, Paragonimidae and Paramphistomidae etc. family members Prasad et al, 2011;Mohanta et al, 2014;Shylla et al, 2011). More localities from South America, North America, Africa and other continents are therefore, to be explored for empathizing host-parasite relationship including the depiction of life cycle stages with their environment along with genotypic variations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identical nature of the ITS2 secondary structure can be attributed to similarity in rRNA biogenesis among eukaryotes; its folding pattern plays an important role in processing of mature rRNA (Joseph et al, 1999) and structures are maintained during evolution through transitions/transversions, although mutations occur frequently (Coleman, 2007;Keller et al, 2010). The utility of ITS2 secondary structure for characterizing parasites has also been demonstrated (Shylla et al, 2011;Ghatani et al, 2012). A high degree of similarity in the ITS2 secondary structures of Posthodiplostomum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian Inference (BI) analysis was also done by aligning the sequences using Clustal X 2.0.7; the NEXUS file format was generated and alignments were imported to Mr.Bayes v3.1.2 programme (Huelsenbeck & Ronquist, 2001), using GTR+I+G model. Markov Chain Monte Carlo (MCMC) chains were generated following Shylla et al (2011) with some modifications: ngen = 250000 (ITS2); 100000 (18S); 200000 (28S); 'sump burnin' = 6250 (ITS2); 2500 (18S); 5000 (28S) and 'sumt burnin' = 6250 (ITS2); 2500 (18S); 5000 (28S). In addition to the sequence data set used in the analysis, Clinostomum sequence was included as the outgroup taxon.…”
Section: Phylogenetic Analysismentioning
confidence: 99%